Disrupsi Digital sebagai Ancaman Eksistensi Media Cetak - Choliq, Abdul (Jurnal Ilmu Komunikasi, 2023)
The proliferation of news stories in online and social media has threatened the print media industry, even today’s many have collapsed; because many printed news outlets often struggle to get clicks from readers that determine advertising revenue. This article reports on the research of the implementation of competitive strategies through a convergence model carried out by print media in response to digital disruption. This research used a qualitative descriptive approach. The study results have revealed that print media companies in the era of digital disruption need to carry out appropriate competitive strategies by converging digital platforms, comprehensive innovation, improving content quality, and creating new business models as well as partnerships with digital influencers as new marketing strategies. In short, today’s print media companies need to improve the quality of news content, combine digital with conventional media, establish partnerships with digital influencers, and design long-term strategies to compete in the digital market